A review of plant leaf fungal diseases and its environment speciation. Issue 1 (1st January 2019) - Jain, Archana; Sarsaiya, Surendra; Wu, Qin; Lu, Yuanfu; Shi, Jingshan
ABSTRACT: There is increasing difficulty in identifying new plant leaf diseases as a result of environmental change. There is a need to identify the factors influencing the emergence and the increasing incidences of these diseases. Here, we present emerging fungal plant leaf diseases and describe their environmental speciation. We considered the factors controlling for local adaptation associated with environmental speciation. We determined that the advent of emergent fungal leaf diseases is closely connected to environmental speciation. Fungal pathogens targeting the leaves may adversely affect the entire plant body. To mitigate the injury caused by these pathogens, it is necessary to be able to detect and identify them early in the infection process. In this way, their distribution, virulence, incidence, and severity could be attenuated. Graphical abstract: uf0001